Analisis Framing Pemberitaan Kasus Pembunuhan Oleh Jendral Ferdy Sambo Terhadap Brigadir Joshua Pada Media Online Kompas.com dan Liputan6.com - Arfian Suryasuciramdhan; Utari Mutiara Ayu; Ilham Arifin; Sahrul Sodikin (Institut Nalanda, 2024)
Premeditated murder or moord is a form of crime against life which is regulated in article 340 of the Criminal Code (KUHP). News of the premeditated murder of Brigadier J on July 8 2022 at the official residence of Inspector General of Police Ferdy Sambo has previously gone viral or trending topics on social media, the case of premeditated murder of Brigadier J who was killed by his own colleague, namely Bharada Richard Eliezer Pudhiang Lumiu alias Bharada E on orders from his superior, Inspector General Pol Fredy Sambo, who serves as head of the Indonesian National Police's propam division. The design in this research uses Robert N. Entman's framing approach. According to Entman, framing is the process of selecting and highlighting certain aspects of reality by the media. The media chooses certain issues to report and ignores other issues, and emphasizes certain aspects of the issues being reported. Framing can be defined as the process of making a message more prominent, meaningful, or remembered by the public. tolerant with the perpetrators, and the law in Indonesia should also be more firm and fair. Compass.com creates a framing so that the public knows that there are many irregularities that occurred in the case of Brigadier J's death, public opinion plays a role in the development of this case, because through social media the news can also be heard. was picked up and went viral so Brigadier J had to get justice. The Ferdy Sambo case is a complex case and full of controversy. The following are several important points that can be concluded from this case: Violation of the Code of Ethics and Law: Ferdy Sambo was proven to have violated the National Police's professional code of ethics and criminal law. He was involved in the planned murder of Brigadier J, as well as making efforts to obstruct the investigation process. Sambo was also proven to have manipulated and engineered the case to protect himself and the other perpetrators. Motive and Behavior The motive for the murder of Brigadier J is still being debated, but strong suspicions point to Sambo's motive for revenge and disappointment towards Brigadier J. Sambo's arrogant, manipulative and authoritarian behavior is in the public spotlight. Impact and Implications.